2018
DOI: 10.1007/s11262-018-1579-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Pestivirus H isolate originating from goats

Abstract: Natural Pestivirus H infections in cattle have been reported worldwide; however, only a few cases of Pestivirus H have been described in non-bovine ruminants such as goats. A new Pestivirus H HN1507 strain was isolated from an infected goat in 2015 and the genome sequence was determined. The full-length genome sequence was 12,556 nucleotides. Phylogenetic analysis, based on the complete genome and Npro fragments, revealed that the isolate belonged to Pestivirus H and was closely related to strains from Italy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Five isolates of the Pestivirus H "a" genotype were detected in Fangcheng and Shangcai in this study (Figures 1, 2). Before this research, Pestivirus H has been previously detected in goats and sheep in Fangcheng (24), and phylogenetic analysis showed that these five isolates were closely related to the HN1507 strain isolated from goat (43). These results indicated that these isolates shared the same origin.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Five isolates of the Pestivirus H "a" genotype were detected in Fangcheng and Shangcai in this study (Figures 1, 2). Before this research, Pestivirus H has been previously detected in goats and sheep in Fangcheng (24), and phylogenetic analysis showed that these five isolates were closely related to the HN1507 strain isolated from goat (43). These results indicated that these isolates shared the same origin.…”
Section: Discussionmentioning
confidence: 68%
“…BLAST analysis of the 5 ′ -UTR and Npro sequences showed that all five Pestivirus H-positive isolates belonged to Pestivirus H. Comparative analysis of the 5 ′ -UTR and Npro region of the Henan isolates and the reference strains of Pestivirus H (TH/04_KhonKaen, HN1507) revealed a sequence identity within the range of 87.5-99.5% and 90.3.2-99.4%, respectively. In particular, the nucleotide homologies between these isolates and the other strain (HN1507) (24,43) isolated from goat in the same area were 97.9±1.6% and 98.6 ± 0.4% in the above two regions.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation